Antiviral susceptibility of influenza A viruses isolated between 2009-2013, in Portugal - Guiomar, Raquel (2013)
Monitoring the influenza antiviral susceptibility had become an important issue in the recent years. The influenza A viruses are naturally susceptible to Neuraminidase inhibitors (NAI) and M2 inhibitors (adamantanes). The increased resistance to oseltamivir and adamantanes (since 2006), the availability and clinical use of influenza antivirals enhanced the need for a close monitoring for loss of susceptibility. Since 2009, at Portuguese National influenza Centre, was developed in the scope of the National Influenza Surveillance Programme a systematic monitoring of antiviral susceptibility (oseltamivir, zanamivir and adamantine). This study shows the results of antiviral susceptibility to NAI and M2 inhibitors for influenza A viruses characterized during 4 winter seasons (2009 to 2013). The phenotypic method, NA inhibition assay, considered the “gold standard” method to determine the susceptibility to oseltamivir and zanamivir, measuring the 50% inhibitory concentrations (IC50) was performed during the study period for a selection of 119 influenza A viruses: 26 and 60 AH1pdm09 from 2009/10 and 2012/13 season, respectively, and 33 AH3 viruses from 2011/12, plus 2 AH3 from the last season were also analysed. Genotypic screening methods were performed for the most common NAI inhibition-reducing substitution, H275Y in AH1pdm09 viruses (n= 340). Matrix gene sequencing, for adamantanes susceptibility surveillance, and neuraminidase gene sequencing were performed for 64 and 119 strains, respectively. In the study period all AH1pdm09 and AH3 viruses, carried the S31N substitution in the M2 protein, which confers resistance to the adamantanes to 100% of the isolates. For the AH1pdm09 the IC50 for oseltamivir ranged from 0.45 to 2.82 (2009/2010) and from 0.15 to 3.27 (2012/2013). The resistance to oseltamivir was identified in 3 AH1pdm09 viruses that carried the H275Y substitution. Two of these viruses were isolated from patients with chronic diseases treated with oseltamivir, a pregnant woman 26 years old with a fatal outcome and an 8 years old child. One of the oseltamivir-resistant virus showed an IC5o value 250-fold higher (IC5o= 502.48) comparing to the susceptible viruses. The AH1pdm09 IC5o values for zanamivir ranged from 0.32 to 3.88 (2009/2010) and from 0.29 to 2.99 (2012/2013). The median IC50 values for oseltamivir and zanamivir were stable between 2009 and 2013. None of the AH1pdm09 isolates presented the other substitutions (D119N, I223R, N295S) associated with reduced susceptibility to NAI. The AH3 viruses analysed in 2011/2012 season showed IC5o values for oseltamivir that ranged from 0.19 to 0.90 and for zanamivir from 0.39 to 0.84. The median IC50 values for oseltamivir and zanamivir were 0.41±1.55 and 0.59±1.21 respectively. In the last season 2012/2013 only two AH3 isolates were analysed and the IC5o values were in the same range of the 2011/2012 AH3 viruses. Since 2009 all the AH3 viruses are susceptible to oseltamivir and zanamivir. None of the AH3 viruses presented the amino acid substitutions known to reduce susceptibility to NAI (E119V/I, R229K, N294S and H274Y). Influenza A viruses isolated in Portugal since 2009 are resistant to adamantanes, which are no longer indicated for influenza A treatment. Otherwise, the resistance to oseltamivir was only observed in a reduced number of strains and all the viruses show susceptibility to zanamivir. The use of conventional sequence analysis and genotypic screening methods for monitoring the molecular markers of antiviral resistance in influenza A virus provides a valuable tool for an early detection of antiviral resistant strains.